Model Pembentukan Budaya Religius di Sekolah Umum - Mutholingah, Siti; Azizah, Khisna (JOM, 2024)
The problem of moral decadence among high school students in this digital era is increasingly widespread. As educational institutions, schools need to develop religious culture to improve students' morals. SMAN 1 Kota Malang is one of the schools that develops religious culture, so even though it is a state school, it has a powerful religious nuance. This research aims to analyze the process of forming religious culture and find a model for forming religious culture at SMAN 1 Kota Malang. This research uses a qualitative case study-type approach with interactive data analysis. The results of this research are (1) the process of forming religious culture at SMAN 1 Kota Malang through 4 stages, namely through providing knowledge and introducing theoretical religious values, religious activities, integration with various scientific fields, and continuous supervision. (2) the model for forming religious culture at SMAN 1 Kota Malang uses an organic-integrative model. This structural-organic-integrative model is a novelty or a new finding in this research. This study implies that it theoretically strengthens and develops the organic model in forming religious culture. Practically, the findings of this study have implications for the discovery of a new model, namely the organic-integrative model, that can be applied by all public schools in developing religious culture.